HYDROLOGICAL DYNAMICS AND RURAL MOBILITY: CONSIDERATIONS ON THE CATTLE TRANSIT IN THE SOUTH PANTANAL IN YEARS OF EXTREME EVENTS: THE DROUGHT OF 2010 AND THE FLOOD OF 2014 - Araujo, Ana Gabriela de Jesus; Teixeira, Débora Luisa Silva; Grilo, Luan Moreira; Silva, Luiz Tadeu da; Oliveira, Gilvan Sampaio de; Monteiro, Antônio Miguel Vieira; Párraga, Guillermo Obregón; Souza, Mônica Tatiane (Ra'e Ga: o Espaço Geográfico em Análise, 2019)
The Pantanal is one of the largest wetlands in the world. In Mato Grosso do Sul, the floodplain stands out on the calf production by the use of native grasslands as pastures. It has as a management characteristic the movement of the herds between lowlands and higher areas, at the pace of the annual floods. The commercialization of cattle for rearing, fattening or slaughtering with other localities consolidates an‘always in motion’livestock farming. Severe hydrometeorological events act as forcings on the management of production, which may impact on increased costs and losses. To contribute to the understanding of the territorial organization of the activity in the region, this study identified the multiannual pattern of cattle traffic at intra and intermunicipal scales and between lowland and plateau areas between 2007 and 2014. In addition, it presented the dynamics of cattle displacement in Aquidauana and Corumbá, municipalities with the largest areas of wetlands and cattle production of the South Pantanal, considering the episodic events of drought in 2010 and full in 2014. The results showed that the flow of cattle presents different levels of connectivity, with emphasis on intra-Pantanal displacement. Increases were observed in the periods of drought and pre-flood and decrease in the flood months; as well as an occasional intense flow in 2014, suggesting an emergency. This endorses adaptive strategies and the need for actions that minimize the impacts of weather and climate variability on cattle breeding in the region.